Spiritual Emptiness: A Critical Analysis of the South Korean Education Perspective of Worldview Islamic Education - Rafdi Ilahi (LECTURES: Journal of Islamic and Education Studies, 2025)
The good quality of education in South Korea still leaves many problems to be solved. The high suicide rate among students, rampant cases of bullying, the differences in quality between private school and public school and high family demands for school achievement are known as education fever. This research is a type of descriptive analysis research, comparing two variables of the education system, namely the South Korean education system and the Islamic education system. Qualitative research method, with data collection from literature that is related to the issues discussed. The problem that occurs in the world of Korean education when viewed from the perspective of Islamic education is the purpose of education itself. Islamic education emphasizes usefulness and human beings who believe and have good morals, while South Korean education aims to change the social strata of families in society. Education is not just a ladder to change social status, but to develop human potential so that they can become caliphs on earth. Not only building intellectual capacity but also spiritual capacity, to provide strength and encouragement in dealing with every failure in life.